2017
DOI: 10.18632/oncotarget.17520
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces autophagy-dependent death in human tongue squamous cell carcinoma cells through DNA double-strand break-mediated oxidative stress

Abstract: Dihydroartemisinin is an effective antimalarial agent with multiple biological activities. In the present investigation, we elucidated its therapeutic potential and working mechanism on human tongue squamous cell carcinoma (TSCC). It was demonstrated that dihydroartemisinin could significantly inhibit cell growth in a dose- and time-dependent manner by the Cell Counting Kit-8 and colony formation assay in vitro. Meanwhile, autophagy was promoted in the Cal-27 cells treated by dihydroartemisinin, evidenced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 46 publications
4
48
0
Order By: Relevance
“…Our previous study found that DHA is selective cytotoxicity for some cancer cell lines, such as head and neck squamous cell carcinoma Cal‐27 and Fadu cells (Shi et al, ; Shi, Wang, et al, ). To test the antiproliferative effect of DHA on human HCC cells in vitro, HepG2215 cells were exposed to DHA (5, 10, 20, and 40 μM) for 12, 24, and 36 hr, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study found that DHA is selective cytotoxicity for some cancer cell lines, such as head and neck squamous cell carcinoma Cal‐27 and Fadu cells (Shi et al, ; Shi, Wang, et al, ). To test the antiproliferative effect of DHA on human HCC cells in vitro, HepG2215 cells were exposed to DHA (5, 10, 20, and 40 μM) for 12, 24, and 36 hr, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that DHA has numerous mechanisms in cancer cell cytotoxicity and autophagy (Guo, ; Shi, Wang, et al, ). Consistent with these studies, the present research provides a novel description for DHA promotion of autophagy via AIM2/caspase‐1 inflammasome (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for this first involves the induction of DNA double‐stranded breaks by DHA while it simultaneously increases the number of γH2AX foci. Consequently, the resultant oxidative stress inhibits the nuclear localization of phosphorylated STAT3 and causes autophagic cell death . The inhibitory effect of DHA on STAT3 is also observed in head and neck squamous cell carcinoma, in which DHA serves as a putative STAT3 inhibitor and blocks JAK2 phosphorylation to induce apoptosis .…”
Section: Signaling Pathways and Cellular Targets Involved In Autophagmentioning
confidence: 96%
“…Shi et al reported that DHA increases Beclin1 expression in human tongue squamous cell carcinoma, thereby promoting autophagosome formation and eventually causing autophagic cell death. The mechanism for this first involves the induction of DNA double‐stranded breaks by DHA while it simultaneously increases the number of γH2AX foci.…”
Section: Signaling Pathways and Cellular Targets Involved In Autophagmentioning
confidence: 99%